Economics pre-service teachers’ knowledge and practices of reflective teaching as predictors of teaching skills in Ibadan (2021)
The study investigated pre-service Economics teachers’ knowledge, perception, and practices of reflective teaching as predictors of teaching skills. The study adopted an ex-post facto design. All Economics pre-service teachers in the University of Ibadan, Ibadan Oyo State, Nigeria were the population. Purposive sampling was used to select departments offering Economics as their teaching subject. In all, a total of Forty-five (45) pre-service teachers participated in the study. Four validated research instruments: Knowledge of Reflective Teaching Test (KRTT) (K-R20=0.87), Pre-service Teacher’s Use of Reflective Practice Questionnaire-PTURPQ (α=0.79), and Teacher’s Classroom Practice Observational Rating Scale (TCPORS) (T=0.770); and Instructional guide for observers (IGO) were used to collect data for this study. The data collected were analysed using Multiple Regression Analysis. Findings of the study revealed that majority of the pre-service Economics teachers had moderate knowledge of reflective teaching, few had low knowledge of reflective teaching and very few had high knowledge of reflective teaching. Also, pre-service teachers’ teaching skills were not significantly affected by knowledge of reflective teaching. The result also revealed that many of the pre-service teachers used reflective teaching occasionally. There was high positive correlation between pre-service teachers’ practice of reflective teaching and teaching skills. Therefore, it is recommended that Pre-service teachers should ensure that their knowledge of reflective teaching is updated and ensures continuous positive perception and use of reflective teaching for improved teaching skills.